Nonalcoholic fatty liver disease: A precursor of the metabolic syndrome. Issue 3 (March 2015) - Lonardo, Amedeo; Ballestri, Stefano; Marchesini, Giulio; Angulo, Paul; Loria, Paola
Abstract The conventional paradigm of nonalcoholic fatty liver disease representing the "hepatic manifestation of the metabolic syndrome" is outdated. We identified and summarized longitudinal studies that, supporting the association of nonalcoholic fatty liver disease with either type 2 diabetes mellitus or metabolic syndrome, suggest that nonalcoholic fatty liver disease precedes the development of both conditions. Online Medical databases were searched, relevant articles were identified, their references were further assessed and tabulated data were checked. Although several cross-sectional studies linked nonalcoholic fatty liver disease to either diabetes and other components of the metabolic syndrome, we focused on 28 longitudinal studies which provided evidence for nonalcoholic fatty liver disease as a risk factor for the future development of diabetes. Moreover, additional 19 longitudinal reported that nonalcoholic fatty liver disease precedes and is a risk factor for the future development of the metabolic syndrome. Finally, molecular and genetic studies are discussed supporting the view that aetiology of steatosis and lipid intra-hepatocytic compartmentation are a major determinant of whether fatty liver is/is not associated with insulin resistance and metabolic syndrome. Data support the novel paradigm of nonalcoholic fatty liver disease as a strong determinant for the development of the metabolic syndrome, which has potentially relevant clinical implications for diagnosing, preventing and treating metabolic syndrome.